Government Authority and Responsibility in the Universal Health Coverage Program from the Aspect of Participation and Financing - Hamidah, Titin; Putera, Andika Persada; Pramono, Budi (RechtIdee, 2024)
Citizens' rights to Social Security are realized by the Government through the National Health Insurance Program (JKN Program) with the principles of Social Insurance. The JKN Program is an initiation to achieve Universal Health Coverage (UHC), which is one of the objectives of the Sustainable Development Goals (SDGs). The government has the authority and responsibility for administering the JKN Program, particularly in terms of participation and financing. This research aims to analyze the Government's authority and responsibility within the JKN Program to achieve UHC. The research is Normative Juridical, using a Juridical approach based on statutory regulations. It concludes that the Government's authority in the JKN Program is legally attributed to the National Social Security Council and the Social Security Administering Body. Concerning the Government's responsibility in the JKN to achieve UHC, the Government must prioritize participation and financing to ensure effective implementation as a part of its obligation to its citizens. BPJS, as a Legal Entity organizing the JKN Program, has Sole Authority and must involve Independent Government Institutions for aspects like service, promotion, and supervision.